Mechanical simulation of reinforced concrete slabs subjected to fire - Bačinskas, Darius; Kaklauskas, Gintaris; Gribniak, Viktor; Geda, Edgaras (Technological and Economic Development of Economy, 2007)
There are many buildings and civil engineering works under construction which are at risk of fire. The fire resistance analysis of reinforced concrete structures constitutes an important part in their design. However, the analysis of the behaviour of load‐bearing members under high temperature conditions is very complicated. Various factors that influence the behaviour of the members need to be taken into account. Analytical and computation methods have been developed in the field of reinforced concrete building exposed to high temperature or accidental fire. Unfortunately, such models are computationally too demanding and their application are limited even for a simply supported reinforced concrete members (beams, plates etc). In this paper, an attempt has been made to extend application of the Flexural model to stress and strain analysis of flexural reinforced concrete members subjected to high temperature. Constitutive models and key material parameters describing thermo‐mechanical behaviour of concrete and reinforcement are discussed. A powerful calculation technique based on layered approach is briefly described. A numerical example of application of present method for calculating of stresses, strains and curvatures of reinforced concrete slab is presented.Article in Lithuanian.Gelžbetoninių plokščių, veikiamų gaisro, modeliavimasSantrauka. Daugeliui civilinių pastatų ir inžinerinių statinių gresia gaisro pavojus. Gelžbetoninių elementų atsparumo ugniai analizė yra svarbi projektavimo dalis. Tačiau laikančiųjų elementų elgsenos analizė, įvertinus gaisro poveikį, yra labai sudėtinga. Turi būti įvertinti įvairūs faktoriai, veikiantys elementų elgseną. Skaitiniams (baigtinių elementų) metodams reikia pernelyg daug kompiuterinių resursų, todėl jų taikymas yra ribotas netgi nesudėtingoms (statiškai išsprendžiamoms) gelžbetoninėms konstrukcijoms (sijoms, plokštėms ir t.t.). Šiame straipsnyje, taikant integralinį sluoksnių modelį, analizuojamas gaisro veikiamų gelžbetoninių konstrukcijų įtempių ir deformacijų būvis. Straipsnyje pateikiamas skaičiuojamasis modelis ir pagrindinės medžiagų savybės, charakterizuojančios šiluminius ir mechaninius pokyčius betone bei armatūroje. Trumpai apžvelgtas efektyvus skaičiavimo būdas, pagrįstas sluoksnių taikymo principu. Pateiktas skaitinis gelžbetoninės plokštes įtempių, deformacijų ir kreivių nustatymo pavyzdys.Reikšminiai žodžiai: šiluminis ir mechaninis modeliavimas, aukšta temperatūra, skaitiniai modeliai, gelžbetonis.First Published Online: 21 Oct 2010